Peer and self assessment in e-learning using moodle and whatsapp as scaffolding to improve students 'ability tobe self-learners - Yuni Gayatri (Universitas Muhammadiyah Surabaya, 2020)
Abstract. Online learning (e-learning) as a solution for learning activities during the Covid19 pandemic in Indonesia. This study aims to describe student learning outcomes in developing Classroom Action Research proposals through the Peer and Self Assessments method in e-learning using Moodle and Whatsapp. The study design was a preexperimental design using One Shot Case Study. The research subjects were students of Biology Education Study Program at the University of Muhammadiyah Surabaya who took the Classroom Action Research course in the even semester of the academic year 2019/2020 with a purposive sampling technique. Data collection techniques through product performance assessment and student response. Data were analyzed descriptively. The results showed that the use of Peers and Self Assessment can encourage students to be actively involved in building knowledge, attitudes, and behavior to become independent learners.